Southeast Asian Transformations Urban and Rural Developments in the 21st Century - Kurfürst, Sandra; Wehner, Stefanie (Global Studies, 2020)
Southeast Asia is one of the most dynamic regions in the world. This volume offers a timely approach to Southeast Asian Studies, covering recent transitions in the realms of urbanism, rural development, politics, and media. While most of the contributions deal with the era of post-independence, some tackle the colonial period and the resulting developments. The volume also includes insights from Southern India. As a tribute to the interdisciplinary project of Southeast Asian Studies, this book brings together authors from disciplines as diverse as area studies, sociology, history, geography, and journalism.